Kualitas Sumber Daya Manusia dan Pertumbuhan Ekonomi Kota Denpasar, Bali (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the impact of human resource quality, as measured by indicators from the Human Development Index (HDI), on economic growth in Denpasar City, Bali. This study utilizes quantitative secondary data collected from the Central Statistics Agency (BPS) for the period 2013 to 2021. This data includes a new method for calculating average years of schooling, life expectancy at birth, per capita expenditure, and economic growth. This study uses panel data regression from five provinces in Denpasar City, Bali, applying classical assumption tests, hypothesis tests, and coefficients of determination. Individually, education level has a significant and negative effect on economic growth in Denpasar City, Bali. Health does not show a significant and negative effect on economic growth in Denpasar City, Bali. While economics has a significant and positive effect on economic growth in Denpasar City, Bali. All three independent variables simultaneously have a significant impact on economic growth in Denpasar City, Bali. The most influential variable is economics.